Coexistence of motor and functional language deficits based on ICD-11 criteria in children with autism spectrum disorder - An exploratory study - Tereza Možná; Hana Válková (Listy klinicke logopedie, 2024)
Autism spectrum disorder (ASD) is a complex neuro-developmental disorder that is characterised by considerable heterogeneity and the occurrence of secondary symptoms, including motor function disorders and disturbances in motor development. The study's main objective was to assess the coexistence of motor and functional language deficits (FL), scaled according to ICD-11 criteria, and standardised evaluation using the motor test for children: The Movement Assessment Battery for Children, 2nd edition (MABC-2). In the research sample (n = 47; 39 boys, 8 girls; age 7-10 years, average age = 8.49; SD = 1.12), the results revealed that 74.5% of the participants had significant motor problems and delays in motor development. Among the participants, 44.7% had no or a slight disability of FL, 21.3% had disturbed FL, and 34.0% had complete or almost complete absence of FL. The results showed a significant positive relationship (R = 0.64; p = 0.005) between the Total Test Score (MABC-2) and the FL involvement, according to the ICD-11 criteria. In this study, better motor performance was significantly associated with smaller FL deficits.